P104 THE INCIDENCE OF INFLAMMATORY BOWEL DISEASE: ANALYZING HISTORICAL TRENDS TO PREDICT THE FUTURE. (7th February 2019) - Coward, Stephanie; Benchimol, Eric; Clement, Fiona; Hazlewood, Glen; Kuenzig, Ellen; McBrien, Kerry; Deardon, Rob; Panaccione, Remo; Seow, Cynthia; Windsor, Joseph W; Kaplan, Gilaad
Abstract: Background: Incidence of Inflammatory Bowel Disease (IBD)—Crohn's Disease (CD) and ulcerative colitis (UC)—is decreasing in some provinces, but increasing in pediatrics. Even with this decrease in incidence, prevalence will continue to rise until incidence equals to mortality. Decision makers require accurate data on the current and future burden of IBD for resource planning to ensure IBD patients receive proper care. Aim: 1) To assess current trends in IBD incidence and forecast future trends; 2) to determine the mortality rate of IBD; and, 3) to calculate the threshold that incidence would need to approximate mortality in order to stabilize the prevalence of Crohn's disease (CD) and ulcerative colitis (UC). Methods: Using population-based data from Alberta (AB), per year incidence is calculated from 2010 to 2015 with an eight-year washout period, stratified by pediatric (<18), adult (18-64), and elderly (65+). Incidence is calculated for CD and UC separately, as well as for total IBD, which includes IBD type unclassifiable. Data is standardized based on annual Canadian age and sex distributions from Statistics Canada. Poisson regression (or negative binomial regression, when appropriate) is used to analyze historical trends and calculate average annual percentage change (AAPC) with 95% confidence intervals (CI). Log-linear models are used to forecast incidence to 2030 with 95% prediction intervals (PI). Overall standardized mortality ratios (SMR) with 95% CI are calculated for IBD, CD, and UC from 2010 to 2015—as compared to the Canadian population. The incidence threshold is calculated to determine an incidence rate that approximates mortality, which would stabilize the prevalence of IBD. Results: Age-stratified IBD, CD and UC incidence with AAPC are provided in Table 1. The incidence of IBD in Alberta is 27.8 per 100, 000 in 2015.The overall IBD incidence is stable from 2010 to 2015 (AAPC= −2.00, 95%CI: −4.15, 0.20) (Table 1). However, the subtype-specific incidence of IBD in adults is decreasing for both CD (AAPC = −5.50; 95%CI: −7.71, −3.23) and UC (AAPC = −4.78; 95%CI: −8.57, −0.84). Figure 1 illustrates the historical and forecasted incidence of IBD, CD, and UC. The SMR is 1.41 (95%CI: 1.34, 1.48) for IBD, 1.48 (95%CI: 1.38, 1.59) for CD, and 1.20 (95%CI: 1.09, 1.31) for UC. The threshold whereby incidence approximates mortality such that it would stabilize the prevalence of IBD is 7.82 per 100, 000. Based on our forecasting models, the incidence of IBD (21.63 per 100, 000; 95%PI: 10.85, 32.41) exceeds this threshold in 2030. Conclusions: The 2030 forecasted incidence (21.6 per 100, 000 persons) exceeds the threshold required to reduce the prevalence of IBD. Future interventional research focused on prevention is urgently required to mitigate the rising burden of IBD. Figure 1: Historical and forecasted incidence (per 100, 000 persons) of Inflammatory Bowel Disease, Crohn's disease, and ulcerative colitis. Historical data is from 2010 to 2015 and forecasted from 2016 to 2030, with 95% prediction intervals represented by shaded area around forecasted incidence (dashed line).